2011
DOI: 10.1016/j.jad.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of suicidality and lithium on gray matter volumes in bipolar depression

Abstract: Reduced GM volumes in critical cortical areas of suicidal patients could be a biological correlate of an impaired ability to associate choices and outcomes and to plan goal-directed behaviors based on a lifetime historical perspective, which, coupled with mood-congruent depressive cognitive distortions, could lead to more hopelessness and suicide. Lithium could exert its specific therapeutic effect on suicide by acting in the same areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 66 publications
6
95
6
1
Order By: Relevance
“…In those with suicidal history, compared to without, there was an increased activation during emotional tasks (such as exposure to emotionally-charged faces) in the rostral ACC, and decreased activation during non-emotional cognitive tasks (such as the IGT (decision-making), or the Go/No-go task (cognitive control)) in the dorsal ACC (van Heeringen et al, 2014). Previous studies have demonstrated decreased grey matter in the OFC, ACC, and prefrontal cortex (PFC) associated with suicide attempts (Benedetti et al, 2011;Monkul et al, 2007), and volume changes of the right amygdala (Monkul et al, 2007). These structural abnormalities may impair the functioning of the amygdalo-orbitofrontal-cingulate network, thereby preventing the amygdala from inhibiting the OFC and PFC, and the OFC from inhibiting the ACC appropriately (de Cates and Broome, 2016).…”
Section: Other Important Findings From Imaging Studiesmentioning
confidence: 99%
“…In those with suicidal history, compared to without, there was an increased activation during emotional tasks (such as exposure to emotionally-charged faces) in the rostral ACC, and decreased activation during non-emotional cognitive tasks (such as the IGT (decision-making), or the Go/No-go task (cognitive control)) in the dorsal ACC (van Heeringen et al, 2014). Previous studies have demonstrated decreased grey matter in the OFC, ACC, and prefrontal cortex (PFC) associated with suicide attempts (Benedetti et al, 2011;Monkul et al, 2007), and volume changes of the right amygdala (Monkul et al, 2007). These structural abnormalities may impair the functioning of the amygdalo-orbitofrontal-cingulate network, thereby preventing the amygdala from inhibiting the OFC and PFC, and the OFC from inhibiting the ACC appropriately (de Cates and Broome, 2016).…”
Section: Other Important Findings From Imaging Studiesmentioning
confidence: 99%
“…Similarly alterations in sleep patterns are a clinically long recognised precipitant and symptom of mood disturbances: most therapeutic work in this regard has explored monoaminergic effects on the thalamus, but there is now evidence for lithium modulating circadian patterns and suprachiasmatic nuclear functioning and expression of clock genes. Lithium's evidenced ability to prevent or partly reverse the grey-matter deficits seen in bipolar patients [Sassi et al 2002] has also been linked to specific therapeutic effects, including its effects on suicidality, potentially through impacting on goal directed behaviour and affecting cognitive distortions [Benedetti et al 2011]. …”
Section: Conclusion: Pulling the Evidence Togethermentioning
confidence: 99%
“…rs334558*C itself was associated with protective effects against gray matter (GM) loss in schizophrenia (Benedetti et al, 2010), whereas other SNPs either directly related to GSK3-b, or to its substrate proteins, were associated with GM volumes in major depressive disorder (Inkster et al, 2009(Inkster et al, , 2010. Lithium administration was followed by an increase of GM volumes in healthy humans (Monkul et al, 2007) and in patients affected by BD (Bora et al, 2010), thus possibly counteracting GM volume reductions in critical cortical areas (Benedetti et al, 2011b). Pivotal prospective studies confirmed that the lithium-associated GM volume increase during treatment correlated with treatment response in BD (Lyoo et al, 2010;Moore et al, 2009).…”
Section: Introductionmentioning
confidence: 99%